PERIODS OF SMALL-AMPLITUDE CEPHEID Y OPH - Usenko, I. A. (Одеські астрономічні публікації, 2017)
Fourier analysis of all 299 RV data for Y Oph collected during last century displayed its mean pulsational period of 17.123024 days with two equidistanted ones, - 17.965158 and 16.355637 days, respectively. The ratio of these periods is near 0.92 with corresponding beat one near 370 days assumes nonradial pulsation of this Cepheid. Furthermore the analysis results provide an availability of one or more companions with orbital periods of 8424.1, 3361.3 days and more. Pulsational period and its amplitude undergo periodical changes, connected, probably with orbital periods, mentioned above.